Mechanisms governing bystander activation of T cells - Yosri, Mohammed; Dokhan, Mohamed; Aboagye, Elizabeth; Al Moussawy, Mouhamad; Abdelsamed, Hossam A. (Frontiers in Immunology, 2024)
The immune system is endowed with the capacity to distinguish between self and non-self, so-called immune tolerance or “consciousness of the immune system.” This type of awareness is designed to achieve host protection by eliminating cells expressing a wide range of non-self antigens including microbial-derived peptides. Such a successful immune response is associated with the secretion of a whole spectrum of soluble mediators, e.g., cytokines and chemokines, which not only contribute to the clearance of infected host cells but also activate T cells that are not specific to the original cognate antigen. This kind of non-specific T-cell activation is called “bystander activation.” Although it is well-established that this phenomenon is cytokine-dependent, there is evidence in the literature showing the involvement of peptide/MHC recognition depending on the type of T-cell subset (naive vs. memory). Here, we will summarize our current understanding of the mechanism(s) of bystander T-cell activation as well as its biological significance in a wide range of diseases including microbial infections, cancer, auto- and alloimmunity, and chronic inflammatory diseases such as atherosclerosis.